The Performance of Shariah Real Estate Investment Trust and Conventional Real Estate Investment Trust in Malaysia - Mohamad, Nor Edi Azhar Binti (UI Scholars Hub, 2016)
This study examines the performances of two Real Estate Investment Trust (REITs) structure in Malaysian capital market by comparing the Dividend Yield (DY), Distribution per Unit (DU), Net asset Value (NAV), and Earning per Unit (EU) of shariah REITSs (iREITs) and conventional REITSs (cREITs) from Malaysia perspective. The secondary data are retrieved from Bloomberg's Database for 13 listed REITs in the Bursa Malaysia main board for a five-year period from 2009 to 2013 with yearly observation. Applying One Way-Anova analysis, an Independent Sample Kruskal-Wallis Test is used to determine any differences in the performance of the two REITs structure. The results provide evidence indicating that the two structures have distinctive and significantly different performances. It also indicates the better performance of iREITs compared to cREITs. The results of this study are useful to provide additional evidence towards the viable of Islamic funds as a significant initiative to broaden and deepen the product base of Islamic capital market in Malaysia.